EXPLORING THE MYTHS AND REALITY OF SALASAR BALAJI - Yadav, Manisha; Rekha Rani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Oral stories/folk narratives have been passed on from generation to generations in order to preserve culture and history. Myth and mythology have always been at the heart of India’s culture. In this process of passing on traditions, the myths originated in particular time periods have changed their forms and are being moulded according to contemporary needs and demands. The paper focuses on one such site of cultural and historical significance in the northern part of India– Salasar. It has now become one of the most popular religious and cultural sites. The place has rich oral history and is surrounded by various myths associated with Balaji in Salasar. The present paper aims to explore the prevalent myths enveloping this site and to analyse that how this place has acclimatised in accordance with the contemporary times and culture and thrive as popular mythical and miracle place.